Financial Gatekeepers : Can They Protect Investors? - Litan, Robert E., 1950-; Fuchita, Yasuyuki, 1958- (Book collections on Project MUSE., 2006)
"Looks at the effectiveness and discusses the appropriateness for further refinement of frameworks designed by policymakers to strengthen investor confidence in corporate financial reporting, especially in the United States and Japan"--Provided by publisher